Carnosic Acid Reverses the Inhibition of ApoE4 on Cell Surface Level of ApoER2 and Reelin Signaling Pathway - Feng, Maoxiao; Cui, Donghai; Li, Yi; Shi, Jian; Xiang, Lan; Bian, Hong; Ma, Zhiyong; Xia, Wen; Wei, Guangwei (Journal of Alzheimer's disease, 2020)
The cell surface level of apolipoprotein E receptor 2 (ApoER2) increases by cyclic transport of ApoER2 and then activates Reelin signaling pathway to exert neuroprotective function in AD. ApoER2 ligand Apolipoprotein E4 (ApoE4) inhibits the recycling of ApoER2 to the cell surface rendering neurons unresponsive to Reelin. Carnosic acid (CA) is proven to possess neuroprotective and neurotrophic functions in Alzheimer's disease (AD) mouse model. However, there are few reports about how ApoE4 impairs the recycling of ApoER2 and if CA can affect the cyclic transport of ApoER2. In this study, we demonstrated that ApoE4 attenuates the binding of sorting nexin 17 (SNX17) to ApoER2 and inhibits the recycling of ApoER2, resulting in decreased cell surface level of ApoER2. Further, we found that CA enhances the binding of SNX17 to ApoER2, counteracts the negative effects of ApoE4 on the cell surface level of ApoER2 to reverse the ApoE4-induced reduction in Reelin signaling activation by increasing the phosphorylation of the N-methyl-D-aspartate receptor (NMDAR) and cAMP-response element-binding protein (CREB) and the expression of Gria2. Thus, CA promotes neurite growth inhibited by ApoE4. Our work suggests that CA may be a potential approach to attenuate the risk of ApoE4-associated AD.